Large intraosseous xanthoma of the mandible – A case report - Brett A. Wilson; Jeffrey H. Brooks; Sloan B. Ashabranner; Franklin B. Ivers (Oral and Maxillofacial Surgery Cases)
Xanthoma is derived from the Greek word xanthos, meaning yellow, and is related to the altered metabolism of lipids resulting in their accumulation in skin, tendon sheaths, and internal organs. Xanthomas manifest as yellowish papules, plaques, or nodules and are characterized by lipid-laden macrophages (foam cells). Xanthoma of bone is extremely rare and, when present, is often secondary to dyslipidemias or endocrine disorders. The former would be considered a secondary intraosseous xanthoma of bone. A xanthoma that is identified within bone in the absence of dyslipidemia or endocrine disease is considered a primary intraosseous xanthoma. When a xanthoma presents in the maxilla or mandible, it is considered an intraosseous xanthoma of the jaw. The first intraosseous xanthoma of the jaw was reported in 1964 and was referred to as a xanthogranuloma of the mandible. Since that initial report, less than 60 total cases have been reported in the English literature. The cases reported are typically small in size and amenable to enucleation and curettage. Our report contributes to the existing literature by providing a unique case example, highlighting the potential for these lesions to progress to a considerable size, impact adjacent anatomical structures, and necessitate more aggressive treatment.